Getting even: occurrence of histopathological primitive melanoma diagnoses three years after the COVID-19 lockdown - Francesco Ricci; Gianluca Pistore; Giovanni Di Lella; Luca Fania; Francesca Ricci; Siavash Rahimi; Annarita Panebianco; Cristina Fortes; Damiano Abeni (Dermatology Reports, 2025)
The COVID-19 lockdown in 2020 caused a significant delay in histopathological melanoma diagnoses in Rome, Italy, leading to an increase in Breslow thickness and more aggressive tumor characteristics in the following years. Although there was a partial recovery in the number of diagnoses in 2021 and 2022, melanoma thickness remained higher than pre-pandemic levels. In 2023, our analysis of primary melanoma cases from the Histopathology Registry of Istituto Dermopatico dell’Immacolata (IDI)-IRCCS in Rome showed that Breslow thickness had finally returned to, or even improved beyond, 2019 levels – indicating a resolution of the diagnostic delay. At the same time, the proportion of ulcerated and nodular melanomas declined. These findings underscore the long-term effects of pandemic-related diagnostic disruptions and highlight the importance of maintaining continuous screening programs, even during public health crises. Ongoing public education on melanoma awareness and early detection remains crucial to preventing future delays.